Vibration control of a flexible beam structure using squeeze-mode ER mount - Jung, W.J.; Jeong, W.B.; Hong, S.R.; Choi, S.-B. (Journal of sound and vibration, 2004)
This paper presents vibration control of a flexible beam structure supported by squeeze-mode electro-rheological (ER) mounts. After devising an appropriate size of the squeeze-mode ER mount, its field-dependent damping forces are evaluated at various exciting frequencies. The damping force controllability of the ER mount is also demonstrated by implementing a proportional integral derivative (PID) controller. The ER mounts are then incorporated with a flexible beam structure subjected to external excitations. The governing equation of the structural system is obtained and an optimal controller which consists of the position and velocity components of the beam structure as feedback signals is designed to attenuate the imposed vibrations. The controller is empirically realized and control responses such as beam acceleration are evaluated in time and frequency domains. In addition, the forces transmitted from the input point (exciting position) to the base plate (mount position) are investigated by applying control voltage and constant voltage.